1999
DOI: 10.1085/jgp.114.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Xenopus laevis Water Nose to Water-Soluble and Volatile Odorants

Abstract: Using the whole-cell mode of the patch-clamp technique, we recorded action potentials, voltage-activated cationic currents, and inward currents in response to water-soluble and volatile odorants from receptor neurons in the lateral diverticulum (water nose) of the olfactory sensory epithelium of Xenopus laevis. The resting membrane potential was −46.5 ± 1.2 mV \documentclass[10pt]{article} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…This has been confirmed by vital staining (Iida and Kashiwayanagi, 1999). The olfactory system is thus tripartite, with both the VN and AC epithelium functioning in aquatic olfaction, the PC epithelium in aerial olfaction.…”
Section: Functional Implicationssupporting
confidence: 53%
See 1 more Smart Citation
“…This has been confirmed by vital staining (Iida and Kashiwayanagi, 1999). The olfactory system is thus tripartite, with both the VN and AC epithelium functioning in aquatic olfaction, the PC epithelium in aerial olfaction.…”
Section: Functional Implicationssupporting
confidence: 53%
“…In X. laevis, which has become the ''model'' amphibian for olfactory studies, Altner (1962) first provided evidence that the adult principal cavity (PC) retains air and the accessory cavity (AC) retains water at all times. This has been confirmed by vital staining (Iida and Kashiwayanagi, 1999). The olfactory system is thus tripartite, with both the VN and AC epithelium functioning in aquatic olfaction, the PC epithelium in aerial olfaction.…”
Section: Functional Implicationsmentioning
confidence: 59%
“…However, the specificity of the different elements of the tripartite olfactory system needs to be discussed as they do not appear to be as strict as could be thought. First, though the PC is exclusively involved in the detection of volatile odorants, the MC is able to detect both volatile and soluble odorants (Iida and Kashiwayanagi, 1999). Second, though Class I ORs are mainly expressed in the MC and Class II ORs in the PC, some class I ORs have also been shown to be present in the PC (Amano and Gascuel, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory marker proteins (OMPs) (Rossler et al, 1998), lectins (Key and Giorgy, 1986;Suzuki et al, 1999;Saito and Tanigushi, 2000), G protein in MC and PC have been found to be different. Third, physiological experiments have shown that PC ORNs detect volatile odorants (Lischka and Schild, 1993;Schild and Lischka, 1994), whereas MC neurons detect soluble odorants, even though they also detect some volatile odorants (Iida and Kashiwayanagi, 1999). Fourth, Freitag et al (1995Freitag et al ( , 1998 showed that class I (fish like) and class II (mammalian like) OR genes were expressed in the MC and the PC, respectively.…”
Section: The Case Of Xenopus Olfactory Systemmentioning
confidence: 99%
“…Calcium‐activated potassium currents are also commonly found except for rat ORNs in culture (Trombley & Westbrook, 1991), which lack the latter. Most of the ORNs have in addition a transient A‐like current similar to ORNs in insects (Zufall et al ., 1991), squid (Lucero & Chen, 1997) and some vertebrates (Firestein & Werblin, 1987; Schild, 1989; Miyamoto et al ., 1992; Corotto et al ., 1996; Ma et al ., 1999) with the exception of lobster, frog and toad (Delgado & Labarca, 1993; McClintock & Ache, 1989; Iida & Kashiwayanagi, 1999). In our conditions we were unable to detect an A‐like potassium current although a prominent A current is present in cultured honeybee Kenyon cells from mushroom bodies (involved in odour processing in insect brain; Schäfer et al ., 1994) and antennal motoneurons from adult honeybee (Kloppenburg et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%